2016
DOI: 10.1016/j.actatropica.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral patterns, parity rate and natural infection analysis in anopheline species involved in the transmission of malaria in the northeastern Brazilian Amazon region

Abstract: The characterization of behavioral patterns allows a better understanding of the transmission dynamics and the design of more effective malaria vector control strategies. This study analyzed the behavioral patterns of the Anopheles species of the Coração district situated in the northeast of the Brazilian Amazon region. The behavioral patterns of the anopheline species were measured based on the 36 collection sites of this district from December 2010 to November 2011. Collections of four hours for three consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 29 publications
7
35
2
1
Order By: Relevance
“…However, studies conducted in peri-urban areas of the city of Macapá, in the state of Amapá, Brazil, demonstrated that it can be a significant regional vector [9][10][11] as well as in Boa Vista, in the state of Roraima [12]. Supporting these findings, in the District of Coração, state of Amapá, A. marajoara was the most frequent species, together with A. darlingi and A. braziliensis, showing anthropophilic behavior and being captured in both indoor and outdoor environments [13,14].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, studies conducted in peri-urban areas of the city of Macapá, in the state of Amapá, Brazil, demonstrated that it can be a significant regional vector [9][10][11] as well as in Boa Vista, in the state of Roraima [12]. Supporting these findings, in the District of Coração, state of Amapá, A. marajoara was the most frequent species, together with A. darlingi and A. braziliensis, showing anthropophilic behavior and being captured in both indoor and outdoor environments [13,14].…”
Section: Introductionmentioning
confidence: 71%
“…Curiously, in the District of Coração, state of Amapá, A. braziliensis was one of the three most abundant and anthropophilic species. It was captured in both indoor and outdoor environments, although it was more abundant outdoors [14]. Thus, A. braziliensis may play some role in malaria transmission when at high density.…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient sampling meant that we could not attribute any significance to this structure. The local abundance of this species in the Amazon River basin varies considerably [ 37 , 67 , 70 ] but it appears to be common in human-modified environments [ 71 ]. The species is highly anthropophilic [ 37 ] and it has been found naturally infected with P .…”
Section: Discussionmentioning
confidence: 99%
“…A great variety of potential vectors have been recorded in the deforested areas of the Amazon [ 30 32 ], but the frequent occurrence of morphologically indistinguishable sibling species, which form species complexes [ 33 ], means that vectors are often misidentified or cryptic species boundaries go undetected [ 34 36 ]. Some vectors, such as Nyssorhynchus triannulatus and Anopheles peryassui , inhabit the forest edge, away from domestic environments and conventional vector control activities, but may be associated with human activity such as deforestation [ 37 ]. Failure to properly elucidate the diversity present in vector species complexes at locations where forest gives way to frontier settlements will likely obstruct the understanding of vector ecology and the Plasmodium transmission cycle associated with deforestation in the Amazon and impede efforts to develop strategies to control frontier malaria [ 10 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…darlingi was considered essentially exophagic/endophagic or both. It also has presented resting behavior indoors (endophily) or outdoors (exophily) and a wide range of peak of biting times and patterns [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%